История налогообложения недропользования за рубежом. (Вестник КазНУ. Серия Экономическая, 2015)
The article is devoted to the history of resource taxes and user fees . These taxes Sunrise menälemniñtreated with a history of use them in the best series.
Keywords: Чужбина